PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS III SDN 001 SIMPANG KELAYANG KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Darwan Darwan; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve learning outcomes IPS Elementary School class III students of the District Kelayang Simpang 001 Kelayang the application of learning models Contextual Teaching and Learning (CTL) in the academic year 2014/2015. Subjects in this study were students of class III Elementary School District of Kelayang Kelayang Simpang 001 Indragiri the number of students 18 students, consisting of 9 men and 9 women. This study is a Class Action Research (Classroom Actions Research) which comprises two cycles. Based on the results of research and data analysis known that an increase in the percentage of activity for teachers to get an average of 78% success with both criteria. Observation of teacher activity in the second cycle to obtain an average of 92% success criteria very well. In addition, the activity of the students during the application of learning models CTL in the first cycle of activity students gain an average of 80% success criteria very well. Implementation of the second cycle of activity students gain an average of 90% success criteria very well. Student learning outcomes before applied learning models CTL is 61.67. At UH 1 first cycle to 74.72 which have increased as much as 21.16%, the number of students who completed 11 students. In the second cycle increased the average value of as much as 18.58% to 88.61. All students completed the implementation of the UH 2. It can be concluded that the CTL learning model can improve student learning outcomes IPS Class III SD N 001 Simpang Kelayang. Keywords: Model Learning Contextual Teaching and Learning, Learning Outcomes IPS